Analysis of the impact of unstructured didactis on social communication - Bonfiglio, Luisa; Torregiani, Giulia; Melchiori, Francesco Maria (Formazione & insegnamento, 2018)
In recent years, the world of scientific research has opened up to new scenarios of didactic intervention, in view of developing, since the pre-school period, social-communicative skills. In this regard, the evidence shows the importance to the use of engaging, interactive, cooperative and experiential activities, that stimulate the natural desire for learning. A potential is recognized in them on the cognitive, relational, social and expressive level, because through this channel the child uses and perfects his verbal and non-verbal languages, creating the conditions for a better use and production of communication. The approach of Educational Neuroscience (EN) shows a clear framework of the links between social and relational competences on the one hand, and cognitive domains on the other, in a vision of didactic experience that shapes the processes underlying cognitive abilities. The Activity Based Intervention (ABI) is an approach used in early childhood programs to incorporate more effective teaching strategies into a child’s daily activities, orienting a naturalistic teaching method that occurs in a usual context such as the preschool classroom. The use of the ABI approach has shown an increase in social competence following the incorporation of social objectives within the educational program. The analysis of this work carried out a statisticalpsychometric comparison of verbal and non-verbal behavior, in children between the ages of 3 and 6, involved in structured and destructured teaching activities (museum education) to highlight the impact of the latter, in learning social skills and analyzing their differences.